Chaucer : A European Life - Turner, Marion, 1976- (Book collections on Project MUSE., 2019)
A groundbreaking biography that recreates the cosmopolitan world in which a wine merchant's son became one of the most celebrated of all English poets More than any other canonical English writer, Geoffrey Chaucer lived and worked at the center of political life--yet his poems are anything but conventional. Edgy, complicated, and often dark, they reflect a conflicted world, and their astonishing diversity and innovative language earned Chaucer renown as the father of English literature. Marion Turner, however, reveals him as a great European writer and thinker. To understand his accomplishment, she reconstructs in unprecedented detail the cosmopolitan world of Chaucer's adventurous life, focusing on the places and spaces that fired his imagination. Uncovering important new information about Chaucer's travels, private life, and the early circulation of his writings, this innovative biography documents a series of vivid episodes, moving from the commercial wharves of London to the frescoed chapels of Florence and the kingdom of Navarre, where Christians, Muslims, and Jews lived side by side. The narrative recounts Chaucer's experiences as a prisoner of war in France, as a father visiting his daughter's nunnery, as a member of a chaotic Parliament, and as a diplomat in Milan, where he encountered the writings of Dante and Boccaccio. At the same time, the book offers a comprehensive exploration of Chaucer's writings, taking the reader to the Troy of Troilus and Criseyde, the gardens of the dream visions, and the peripheries and thresholds of The Canterbury Tales. By exploring the places Chaucer visited, the buildings he inhabited, the books he read, and the art and objects he saw, this landmark biography tells the extraordinary story of how a wine merchant's son became the poet of The Canterbury Tales.